Anterior cruciate ligament injury mechanisms through a neurocognition lens: implications for injury screening - Gokeler, Alli; Benjaminse, Anne; Della Villa, Francesco; Tosarelli, Fillippo; Verhagen, Evert; Baumeister, Jochen (BMJ Open Sport & Exercise Medicine)
Athletes in team sports have to quickly visually perceive actions of opponents and teammates while executing their own movements. These continuous actions are performed under time pressure and may contribute to a non-contact ACL injury. However, ACL injury screening and prevention programmes are primarily based on standardised movements in a predictable environment. The sports environment provides much greater cognitive demand because athletes must attend their attention to numerous external stimuli and inhibit impulsive actions. Any deficit or delay in attentional processing may contribute to an inability to correct potential errors in complex coordination, resulting in knee positions that increase the ACL injury risk. In this viewpoint, we advocate that ACL injury screening should include the sports specific neurocognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine